2004
DOI: 10.1289/ehp.7345
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Anchoring of Gene Expression Changes during Estrogen-Induced Uterine Growth

Abstract: A major challenge in the emerging field of toxicogenomics is to define the relationships between chemically induced changes in gene expression and alterations in conventional toxicologic parameters such as clinical chemistry and histopathology. We have explored these relationships in detail using the rodent uterotrophic assay as a model system. Gene expression levels, uterine weights, and histologic parameters were analyzed 1, 2, 4, 8, 24, 48, and 72 hr after exposure to the reference physiologic estrogen 17β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
67
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 56 publications
(59 reference statements)
9
67
0
1
Order By: Relevance
“…Previous studies have demonstrated that estrogens induce dramatic increases in uterine wet weight, luminal epithelial cell height, stromal thickness, and BrdU labeling (Carthew et al, 1999;Moggs et al, 2004b;Kwekel et al, 2005). In contrast, TCDD did not induce alterations in any of these histological or morphological endpoints (data not shown).…”
Section: Comparison Of Uterine Gene Expression Responses To Tcdd and Eementioning
confidence: 62%
See 1 more Smart Citation
“…Previous studies have demonstrated that estrogens induce dramatic increases in uterine wet weight, luminal epithelial cell height, stromal thickness, and BrdU labeling (Carthew et al, 1999;Moggs et al, 2004b;Kwekel et al, 2005). In contrast, TCDD did not induce alterations in any of these histological or morphological endpoints (data not shown).…”
Section: Comparison Of Uterine Gene Expression Responses To Tcdd and Eementioning
confidence: 62%
“…To independently examine the estrogen-like gene expression responses of TCDD, six genes were chosen for verification by QRTPCR. Arginine-rich, mutated in early stage tumors (Armet), asparagine synthetase (Asns), activating transcription factor 4 (Atf4), expressed in nonmetastatic cells 1 (Nme1), proliferating cell nuclear antigen (Pcna), and solute carrier family 25 member 5 (Slc25a5) were specifically selected because they displayed similar responses to EE and TCDD and have been previously identified as estrogen inducible in the rodent uterus in independent studies (Watanabe Fertuck et al, 2003;Moggs et al, 2004b;Kwekel et al, 2005). QRTPCR analyses confirmed the microarray results indicating these genes were induced by both EE and TCDD (Fig.…”
Section: Comparison Of Uterine Gene Expression Responses To Tcdd and Eementioning
confidence: 99%
“…One of highest (> 4-fold) increase in retinal ganglion cells after injury (rat) Morris (54) Development and morphogenesis (breast) SPRR1A, 2A, 2B 6-12 fold increase as breast bud penetrates mesenchyme (mice) Robertson (55) Development and morphogenesis (prostate) SPRR2A Upregulated during prostate development and carcinogenesis in prolactin receptor knockout mice (mice) Moggs (56) Hormone-responsive remodeling (uterus) SPRR1,2 5-60-fold estrogen-induced upregulation during uterine epithelial remodeling (mice) Park (57) Development and morphogenesis (colon) SPRR2A Four-fold or greater increase of between E13.5 and E18.5 development, associated with "differentiation". CAAGGCGTGTTCTGTCTCAA mVIMENTIN AAGGAAGAGATGGCTCGTCA TTGAGTGGGTGTCAACCAGA mE-CADHERIN GTCAACACCTACAACGCTGCC GTTGTGCTCAAGCCTTCAC mGAPDH TGGCAAAGTGGAGATTGTTGCC AAGATGGTGATGGGCTTCCCG mS100A4 TTGTGTCCACCTTCCACAAA GCTGTCCAAGTTGCTCATCA hSPRR2A AGTGCCAGCAGAAATATCCTCC TGCTCTTGGGTGGATACTTTGA hβ-ACTIN AGGCATCCTCACCCTGAAGTA CACACGCAGCTCATTGTAGA …”
Section: Sprr1amentioning
confidence: 99%
“…However, it has been demonstrated that E2 and DHT trigger distinct effects on the thickness and morphology of epithelial cells layer as well as on the edematous appearance of stromal cells [3]. Both hormones, particularly E2 after 4h, provoke a major influx of fluid into the uterus, and this increased vascular permeability is in part due to an increased mRNA expression of the vascular endothelial growth factor (VEGF) [18]. Indeed, in our previous studies VEGF mRNA expression was up-regulated by 6.7-fold and 3-fold at 3h following E2 or DHT administration, respectively [4,20], which supports its involvement in the regulation of vascular permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the greater risk of breast cancer, deleterious effects on cardiovascular systems and other negative effects attributed to progestins [9,10] reinforces the use of a combination of estrogens and androgens as HRT in menopausal women [11][12][13]. In the mouse, while the estrogenic stimulation of proliferation of uterine epithelial and stromal cell growth and differentiation is well documented [14][15][16][17][18][19][20] the observation that DHT also exerts modulatory effects on these cells is known but not elucidated [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%